In vivo and in vitro studies of fetal hemoglobin induction by hydroxyurea in β-thalassemia/hemoglobin E patients - Yuwadee Watanapokasin (2018)
Objective. Some, but not all, β-thalassemia/hemoglobin E (β-thal/HbE) patients respond to hydroxyurea treatment. It would be helpful if patient responses to hydroxyurea could be screened in vitro to identify responders and nonresponders before beginning in vivo treatment. Materials and Methods. Thirteen β-Thal/HbE patients were treated with hydroxyurea orally for 2 years at a starting dose of 5 mg/kg/day for 5 days/week with escalation to a maximum of 10 mg/kg/day. For comparison, erythroid cells obtained from peripheral blood of the same patients 1 year after they had stopped hydroxyurea treatment were treated with hydroxyurea in vitro. The γ-globin mRNA was measured by real-time reverse-transcription polymerase chain reaction, fetal hemoglobin (HbF) by high-performance liquid chromatography,Gγ- andAγ-globin chains by Triton X-100 acid urea polyacrylamide gel electrophoresis. Results. Treatment of cells in primary culture with 30 μM hydroxyurea for 96 hours significantly increased the fractional HbF content in β-Thal/HbE patients. TheGγ:Aγ-globin mRNA was induced 0.30- to 8-fold in vitro and 0.30- to 6-fold in vivo (r2= 0.51, p = 0.16 by paired t-test); the fractional HbF content was induced 0.50- to 19-fold in vitro and 0.30- to 12-fold in vivo (r2= 0.61, p = 0.20) and theGγ:Aγ-globin chain ratio was increased 0.80- to 1.40-fold in vitro and 1- to 1.20-fold in vivo (r2= 0.62, p = 0.13). Conclusion. The correlation of in vivo and in vitro results of HbF synthesis and globin mRNA suggest that in vitro testing may predict the in vivo response. © 2005 International Society for Experimental Hematology. Published by Elsevier Inc.